Affecting factors of youth health reproductive information access in health Faculty of University in Surakarta – 2018 - Meutia Fildzah Sharfina (BKM Public Health and Community Medicine, 2021)
Objective: Reproductive health in adolescents is important to be a better future provision knowledge. This is supported by the existence of information access. Information access reproductive health is affected by several factors, including the barriers. The purpose of this research is to analyze the factors that are associated with access to information on youth health reproductive information access in one University of Surakarta. Method: This research is using observational with cross-sectional. The data analysis used was Chi Square. Independent variable were discussion with parents, economic barriers, cognitive barriers, and psychosocial barriers. Dependent variable was discussion with parents, economic barriers, cognitive barriers, and psychosocial barriers. The technique of data collection is done by a questionnaire filled out by respondents related discussion with parents, economic barriers, cognitive barriers, and psychosocial barriers affecting to youth health reproductive information access.. Results: The results has shown that factors which related were cognitive barriers (p=0.022) whereas 44.34% of respondents experienced cognition aspect barriers in the form of respondent knowledge related to where to get reproductive health services and information. In the data collection, 111 respondents knew the existence of health care places that provide reliable information about reproductive health and many of them stated that puskesmas is a place that provides such services although there are many other sources such as LSM, PIKM, PKPR, GenRe, and others. Conclusion: The university is expected to add more informations related to the reproductive health through the development of education by activating a program in collaboration with BKKBN namely PIKM so that students who want to get more in-depth reproductive health information become easier and helped.